Identifying the Impact of Work Experience and Compensation on Employee Performance - Hartono, Drajat; Barus, Imelda; Susilowati, Teti; Nurhayati; Santoso, Aprih (Indonesian Journal Economic Review (IJER), 2025)
This study aims to examine the impact of work experience and compensation on employee performance in state-owned enterprises (SOEs). A quantitative approach with regression analysis was employed, involving 110 respondents selected using a purposive sampling technique. Respondents were SOE employees with at least five years of service, who provided data through questionnaires. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that both work experience and compensation significantly affect employee performance. These results can serve as a reference for management to identify key factors influencing employee performance, supporting the achievement of organizational goals.